SISTEM PIDANA DAN PEMIDANAAN DI DALAM PEMBAHARUAN HUKUM PIDANA INDONESIA - Failin Alin (JCH (Jurnal Cendekia Hukum), 2017)
Renewal of criminal law in the context of improving the punishment system is still continuing. Of the many things to be updated, one important thing in the penal system is also crucial provided in the reform of Indonesian criminal law is the structural punishment system. This is something that should be included in the concept of reform of criminal law. Barda Nawawi termed as an integral policy in the handling crime to mention the importance of structural punishment system, which also means integral policy in the punishment system. The problems that arise are how the criminal system and punishment in the current Penal Code and  the Criminal System and Penalties in the New Criminal Code Concept as Part of the Renewal of Indonesian Penal Law. While the research method The type of research conducted is legal juridical Normative research that is about what the concept of punishment system in the renewal of criminal law in Indonesia that is by collecting data normatively and what is in the Act related to criminal law. In this paper we discussed it can be simply described, so far in the criminal system in Indonesia the focus of criminal offense and criminal responsibility is on the direct individuals involved in the criminal process. Where  is often the involvement of other parties besides the individual concerned who can also be held accountable as the impact of the occurrence of a crime. A concrete example, if a child commits a criminal offense, his / her "criminal" is not only granted to the child, but to his / her parents even if the criminal sanction is for example a fine of fines. This is because using the logic that the child is still the responsibility of parents, so that parents are also responsible for the actions of his son.